Ночное апноэ у пациентов с артериальной гипертензией и метаболическим синдромом. Влияние сипап-терапии - Т. Н. Ермолаева (SINAPS LLC, 2014)
In recent years in cardiology actively studied the problem of breathing during sleep in connection with the fact that accumulate more and more data on the value of breathing during sleep in the development of cardiovascular disease, including fatal complications. In particular, great attention is paid to obstructive sleep apnea (OSA), as the condition is most clearly associated with cardiovascular disease. The prevalence of OSAS varies greatly in different study populations, and epidemiological data for Russia are practically absent. As the mechanism responsible for the increase in blood pressure in patients with OSA is usually considered activation of the sympathetic nervous system due to episodes of sleep apnoea. This pathophysiological process is also an important factor in the development of arterial hypertension in obesity. The results of researches, studying the mechanisms of interaction between obesity and OSA, very mosaic. Since OSA sleep much upset and is accompanied by episodes of hypoxia, there is nothing surprising that the secretion of hormones, usually having a circadian daily fluctuations, is also changed. These problems and devoted presented in this article the literature review.